Safety, Tolerability, and Pharmacokinetics (PK) of Posaconazole (POS) Intravenous (IV) Solution and Oral Powder for Suspension in Children With Neutropenia. (4th October 2017) - Groll, Andreas H; Abdel-Azim, Hisham; Lehrnbecher, Thomas; Steinbach, William; Murray, RoseAnn; Paschke, Amanda; Mangin, Eric; Winchell, Gregory A; Bruno, Christopher J
Abstract: Background: POS, a triazole antifungal approved for prophylaxis and treatment of adults with invasive fungal infections, is available as an IV solution and 2 oral formulations: an oral suspension and a tablet with improved bioavailability. A novel powder for oral suspension (PFS) has been developed to offer the bioavailability of the tablet in a formulation optimized for weight-based dosing in children. The objective of this study is to evaluate the safety, tolerability, and PK of POS IV and POS PFS in pediatric patients (patients) aged 2 to 17 y with documented or expected neutropenia. Methods: This is an ongoing, nonrandomized, multicenter, open-label, sequential dose-escalation study evaluating POS IV and POS PFS. Pts are divided into 2 age groups: 2 to <7 and 7 to 17 y. Each age group includes 2 dose cohorts: 3.5 mg/kg/d and 4.5 mg/kg/d. Patients received 10–28 d of POS initially as IV solution with the option to switch to PFS after 10 d for the remainder of the treatment period. PK sampling was conducted after 7–10 days on each formulation. Target PK exposure was ~90% of patients with Cavg 500–2, 500 ng/mL. Cavg is defined as AUC over a dosing interval. Results: 57 of 66 patients (86%) who received POS IV were PK evaluable; 35 patients (53%) received POS PFS, of whom 30 (86%) were PK evaluable. Table 1 shows Cavg and proportion in target range of PK-evaluable patients by dose cohort and age group. The safety profiles of POS IV and PFS were similar to those previously reported for adults treated with oral/IV POS. Conclusion: POS PFS resulted in lower POS exposure than IV across age groups at both dose levels. POS exposure was substantially lower in the younger age group for both IV and PFS. At 4.5 mg/kg, the patients in this study achieved the predefined target but did not achieve systemic exposures (mean Cavg ) comparable to those seen in adults with POS IV or tablet. These results suggest that study of POS IV and PFS dosing >4.5 mg/kg/d is warranted. Disclosures: A. H. Groll, Merck Sharp & Dohme: Consultant, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee and Speaker honorarium. T. Lehrnbecher, Merck/MSD: Scientific Advisor and Speaker's Bureau, Speaker honorarium. Astellas: Scientific Advisor and Speaker's Bureau, Speaker honorarium. Basilea: Scientific Advisor, Consulting fee. Gilead: Investigator, Scientific Advisor and Speaker's Bureau, Research grant and Speaker honorarium.Pfizer: Speaker's Bureau, Speaker honorarium. W. Steinbach, Merck: Consultant, Consulting fee. Astellas: Consultant, Consulting fee. Gilead: Consultant, Consulting fee. R. Murray, Merck: Employee, Salary. A. Paschke, Merck: Employee, Salary. E. Mangin, Merck: Employee, Salary. G. A. Winchell, Merck: Research Contractor, Consulting fee. C. J. Bruno, Merck: Employee and Shareholder, Salary and Stock.